Specifics of Foreign Assistance Allocation under the Trump Administration: From Inauguration to ‘Ukrainegate’ - V. I. Bartenev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2020)
This paper identifies and explains the most characteristic substantial and procedural features of the U.S. foreign assistance allocation under Donald Trump. The research covers a 3-year period from the inauguration of the 45th President of the United States to the Ukrainegate — the first scandal in the U.S. history provoqued by the submission of an anonymous whistleblower’s report pointing at the President’s illegal manipulation of the foreign aid resources to achieve personal political goals, which paved the way to his impeachment. The first section examines the particularities of the Trump and his administration’s conceptual approach to the utilization of foreign assistance tools for political purposes. The second section depicts the process of instrumentalization of these concepts, as well as a confrontation between the White House and the Capitol Hill over foreign aid budgets and their implementation. The final section identifies common and unique features of three exemplary cases of aid suspension — towards Pakistan, the Northern Triangle countries (Guatemala, Honduras and El Salvador) and Ukraine. The conclusion is drawn that from the very beginning Donald Trump had promoted an extremely pragmatic, transactionalist approach to foreign assistance with aid allocation regarded as a mutually beneficial transaction meant to bring concrete and often short-term dividends. Adherence to this approach manifested itself in various forms — in the Predisent’s public statements, in the rhetoric of his administration’s key doctrinal documents and budget proposals, and also in the White House’s regular attempts (futile though) to cut aid to countries which did not provide anything in return, and to prepare the ground for rescinding the unobligated aid funds appropriated by the Congress. The most quintessential element of transactionalism in foreign aid policies was a wide use of aid suspension tools which provided the United States with a costless method to coerce its counterparts to make concessions. The Ukrainian case is, undoubtedly, totally different from the cases of suspension of aid to either Pakistan or the Northern Triangle countries but illegal actions attributed to Trump, as well as his political opponents’ treatment of these actions followed the logic of his presidency and exemplified an unprecedented politization of foreign aid allocation process. The latter trend should be interpreted in the context of a traditional confrontation of the White House and the Congress over the limits of presidential authority in foreign policy and budget implementation. Foreign assistance has become the domain where these two dimensions overlapped generating a cumulative effect of an extreme scale manifested by the Ukrainegate and its aftermath.